Long, low intensity endurance sessions: When is Low too low? When is Long too long? - Seiler, S. (University of Agder, 2020)
We know that successful, sustainable endurance training includes a lot of LIT- low-intensity training. But, it is not very common to have athletes do 4 hour training rides in the laboratory, so we do not have a lot of research on this vital component in endurance training. In this video, I zoom in on LIT sessions and begin to lay out a process for individually determining what intensity and duration to use for these sessions. (37:27 Minuten)